Analysis of Health Level Assessment of Sharia Saving-Loan and Financing Cooperative - Muhammad Ridwan Ibrahim; Zumratul Meini (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2022)
In running their business, cooperatives need to conduct performance evaluation to determine its health level and improve the quality in the following years. KSPPS BMT Huwaiza is one of the cooperatives that provides loan and financing with mudharabah, murabahah, and ijarah contracts. In the midst of this Covid-19 pandemic, BMT Huwaiza managed to get government trust to receive revolving fund in order to support its activities. Thus, it is important to analyze the health level of BMT Huwaiza considering that this cooperative is responsible for the sustainability of the revolving fund. The performance evaluation on KSPPS BMT Huwaiza in 2017 - 2019 resulted in a health level of